Repensando un nuevo modelo ciudad post-COVID-19 - Rodríguez, José Gesto (Universidad de Boyacá, 2021)
At present, many researchers are focused on exploring the dynamics of the pandemic in urban areas to understand its impacts on cities. Certainly, this health crisis has left an indelible mark on the daily life of large human settlements, forcing us to rethink their development in different dimensions. In particular, the urban discipline has the challenge of generating novel models that manage to maintain the balance between the new concept of social distancing and the proposals that combine creative effort, as well as the adequate use of available resources in the fight against COVID-19 and other future impacts. The following is an analysis of recent scientific literature; by reviewing theoretical benchmarks that show how cities can rethink their urban policies to strengthen their risk preparedness and response capacity, and become more resilient, smart, sustainable and inclusive.